2015
DOI: 10.5455/gulhane.154738
|View full text |Cite
|
Sign up to set email alerts
|

Oral hygiene and oral health status of the nursing students in Turkey

Abstract: Oral hygiene and oral health status of the nursing students in Turkey Mehmet Vehbi BAL (*), Umut BENGİ (*), Cengizhan AÇIKEL (**), Işıl SAYGUN (*)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
1
3
0
1
Order By: Relevance
“…Gökalp et al [ 12 ] reported a mean DMFT estimation of 2.3 in their study in 15-year-old patients; Keles et al [ 11 ] in their study reported a mean DMFT of 2.37. Namal et al [ 13 ] detailed a mean DMFT estimation of 4.96 in participants aged 18–19 years, and Bal et al [ 14 ] reported a mean DMFT estimation of 4.26 in nursing undergraduates, and in this investigation, we saw that the participant’s mean DMFT values were either equivalent to or lower than the mean DMFT estimations of the participants of a similar age range revealed in previously mentioned examinations.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Gökalp et al [ 12 ] reported a mean DMFT estimation of 2.3 in their study in 15-year-old patients; Keles et al [ 11 ] in their study reported a mean DMFT of 2.37. Namal et al [ 13 ] detailed a mean DMFT estimation of 4.96 in participants aged 18–19 years, and Bal et al [ 14 ] reported a mean DMFT estimation of 4.26 in nursing undergraduates, and in this investigation, we saw that the participant’s mean DMFT values were either equivalent to or lower than the mean DMFT estimations of the participants of a similar age range revealed in previously mentioned examinations.…”
Section: Discussionsupporting
confidence: 64%
“…In this study, 62% of the participants mentioned that they brushed their teeth once every day and 28% mentioned that they brushed their teeth twice every day. Bal et al [ 14 ] found that 88.9% of nursing undergraduates brushed their teeth at least twice every day. In this examination, just 38.5% of the participants in almost same age-group mentioned brushing their teeth once every day.…”
Section: Discussionmentioning
confidence: 99%
“…However, different DMFT values in similar age groups have been reported in other studies. Gökalp et al [15] reported a mean DMFT value of 2.3 in adolescents aged 15 years old, Bal et al [16] reported a mean DMFT value of 4.26 in nursing students, and Namal et al [17] reported a mean DMFT value of 4.96 in participants aged 18–19 years old. In the present study, we observed that the individuals’ mean DMFT values were either equal to or lower than the mean DMFT values of individuals of the same age group reported abovementioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, 11.5% of the students stated that they never brushed their teeth, whereas 43.4% stated that they had never been to the dentist. Bal et al [16] found that 88.9% of nursing students brushed their teeth at least twice a day. In our study, only 38.5% of the students in the nearly same age group reported brushing their teeth at least once a day.…”
Section: Discussionmentioning
confidence: 99%
“…Konuyla ilgili yapılan literatür incelemesinde diş çürükleri ve periodontal hastalıkların ne olduğu, primer sebepleri, klinik belirtileri ve hastalıkları önlemenin yollarını ele alan uluslararası ve ulusal literatürde az sayıda çalışma yer almaktadır (6)(7)(8)(9). Türkiye'de yapılan çalışmalarda, hastaların bilgi düzeyi ve ağız sağlığı davranışları açısından tutarsız olduğu ve uzmanlar tarafından verilen ağız sağlığı eğitimine yönelik karşılanmamış bir gereksinim olduğu gösterilmektedir (5,10,11).…”
unclassified